Pengelolaan Instagram @pemkabbekasi Dalam Penyebaran Informasi Publik - Anggraeni, Ratna; Solahudin, Dindin; Ma’arif, Abdul Aziz (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2024)
This study aims to describe the management of Instagram @pemkabbekasi in disseminating public information through the concept of The Circular Model of SoMe proposed by Regina Luttrell. The method used in this research is descriptive method with data collection techniques in the form of in-depth interviews, observation, and documentation. The results showed that the Instagram management carried out by @pemkabbekasi was divided into several stages. First, determining social media and interacting with the public in order to gain public trust. Second, filtering issues that develop in the community and collaborating with related agencies to produce accurate information and then the information obtained is packaged into interesting content. Third, media monitoring as an evaluation of the activities and interactions that occur through Instagram. Fourth, utilizing hashtags and reels and collaborating with talent.